Rapid elevation of brain-derived neurotrophic factor production in the bilateral trigeminal ganglia by unilateral transection of the mental nerve in mice. Issue 8 (1st April 2021) - Yamazaki, Maiko; Tsurumaki, Tatsuru; Yamada, Yurie; Maeda, Takeyasu; Seo, Kenji
Abstract : Objectives: Previous spinal nerve injury studies have reported brain-derived neurotrophic factor (BDNF) mRNA upregulation in either the ipsilateral dorsal root ganglion (DRG) neurons or both the contralateral and ipsilateral DRG neurons from early period after peripheral nerve injury. This BDNF elevation induces hyperalgesia in the injured and/or uninjured sites, but this detailed mechanism remains unknown. This study aimed to investigate the BDNF mRNA expression in bilateral DRG neurons caused by unilateral nerve injury and to explore the possible mechanisms by which nitric oxide (NO) mediates BDNF production in the DRG, resulting in contralateral hyperalgesia. Methods: Early changes in BDNF mRNA expression in the bilateral trigeminal ganglia, within 1 day after mental nerve transection, were examined. Additionally, the effects on BDNF production of the NO synthase inhibitor N(ω)-nitro-l -arginine methyl ester (L-NAME) were investigated in the bilateral trigeminal ganglia. The relationship between injured neurons and BDNF production in the trigeminal ganglia was then assessed using immunohistochemical and retrograde tracing methods. Results: Reverse transcription-PCR analysis demonstrated that unilateral transection of the mental nerve induced a rapid elevation of BDNF mRNA expression, which was inhibited by the intracerebroventricular administration of L-NAME prior to nerve transection. This effect was observed in both the ipsilateral and contralateral sides to the nerve transection. BDNF immunostaining combined with FluoroGold retrograde tracing revealed two types of BDNF-reactive neurons, FluoroGold-labelled and non-FluoroGold-labelled neurons, in the ipsilateral and contralateral sides of the trigeminal ganglia. BDNF-positive cells were also observed in the trigeminal ganglia of other trigeminal nerve branches. Conclusions: Unilateral nerve injury upregulates BDNF production in the bilateral trigeminal ganglia by NO-mediated and/or indirect activation of afferent neurons, resulting in contralateral hyperalgesia.